Leading the pack innovations in food packaging - Leigh, Richard; Video Educational Australasia (Australia : Video Educational Australasia, 2001)
This program look at 10 innovative food packaging products including CSIRO's biodegradable plastic, winners of the Packaging Council of Australia industry awards, plastic bags that'breath' like paper and packaging techniques of the future
Title from title screen
Executive producer, Neil Barrett ; editor, Angela Schroeder ; graphic, Reece Sanders ; camera, Richard Leigh...[et al.]
Narrator: Gary Newton
Keywords: Food -- Packaging; Food -- Packaging -- Technological innovations